The Transmission of Financial Stress from Advanced to Emerging Economies - Danninger, Stephan (IMF Working Papers; Working Paper ;, 2009)
This paper studies how financial stress is transmitted from advanced to emerging economies, using a new financial stress index for emerging economies. An episode of financial stress is defined as a period when the financial system's ability to intermediate may be impaired. Previous financial crises in advanced economies passed through strongly and rapidly to emerging economies. In line with this pattern, the unprecedented spike in financial stress in advanced economies elevated financial stress across emerging economies above levels seen during the Asian crisis, but with significant cross-country variation. The extent of pass-through of financial stress is related to the depth of financial linkages between advanced and emerging economies. The paper finds that higher current account and fiscal balances do little to insulate emerging economies from the transmission of financial stress in advanced economies. However, they may help dampen the impact on the real sector of emerging economies and help reestablish financial stability and foreign capital inflows once financial stress subsides.